Respostas
respondido por:
3
11x - (-3x+10) = 4x +2
11x +3x -10= 4x +2
14x -4x = 2 +10
10x =12
x= 12/10 simplificando fica: x=6/5
11x +3x -10= 4x +2
14x -4x = 2 +10
10x =12
x= 12/10 simplificando fica: x=6/5
jaanainaevelyn:
posso mandar outra
respondido por:
2
11x - ( - 3x + 10) = 4x + 2
11x + 3x - 10 = 4x + 2
14x - 10 = 4x + 2
14x - 4x = 2 + 10
10x = 12 (:2)
5x = 6
x = 6/5
11x + 3x - 10 = 4x + 2
14x - 10 = 4x + 2
14x - 4x = 2 + 10
10x = 12 (:2)
5x = 6
x = 6/5
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás